PENGARUH HARGA, PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN KONSUMEN DI WARUNG MAKAN BERKAH PADANG PARIAMAN - Agus Nurofik; Nini, Nini; Sutiyem, Sutiyem; Dessy Trismiyanti; Yoserizal, Yoserizal (Bajang Institute, 2024)
This research aims to determine the influence of price, promotion and product quality on consumer purchasing decisions at Warung Makan Berkah. The research method used is quantitative descriptive. The research results show that price, promotion and product quality have a significant and positive influence on consumer purchasing decisions. Simultaneously, these three factors are also significantly interconnected and have a positive influence on consumer purchasing decisions. Increasing purchasing decisions is necessary to increase sales of service products in the long term. Price, promotion and product quality are factors that may have an influence on consumer purchasing choices for food. Researchers conducted this research to find out whether price, promotion and product quality have an influence on consumer decision making regarding food purchases at Warung Makan Berkah. The type of research carried out in this research is descriptive quantitative by distributing questionnaires to 100 consumers at the Makan Berkah stall. The multiple regression method was used for data analysis with the Statistical Package of Social Sciences (SPSS) application to carry out the calculations. SPSS is a statistical data processing software application. Based on research conducted by researchers, the results of this research show that the price of a food product will have a significant effect and be positively related to customer perceptions of consumer decisions. Apart from that, the quality of service products also has a significant effect and is positively related to customer perceptions of consumer decisions, and sales promotions also have a significant effect and is positively related to customer perceptions of consumer decisions. And simultaneously the factors of price, promotion and product quality are significantly interconnected and have a positive influence on customer perceptions of consumer purchasing decisions